2014
DOI: 10.1089/sur.2013.083
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Different Virus-Specific CD8+ T Cells after Kidney Transplantation

Abstract: Patients who were positive for any virus had a significantly greater risk of developing complications of viral disease during the 6-mo follow-up period in the study (p=0.026), suggesting a general susceptibility to viral reactivation. The evaluation of virus-specific CD8+ T-cells may prospectively help to identify patients at risk for viral reactivation after KTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The commercially developed iTAg TM [Ni 2+ -nitrilotriacetic acid (NTA)–His-tag Chelate complexes] class I MHC Tetramers (Beckman Coulter, Krefeld, Germany) allow the staining of epitope-specific CD8 + T lymphocytes [ 85 ]. Mees et al evaluated the CMV-specific CD8 + T lymphocytes in 23 kidney transplant recipients using the CMV-specific iTAg TM class I pMHC Tetramers (Beckman Coulter, Germany) with the CMV-Ag specific pMHC-tetramers restricted by five different HLA-A and HLA-B alleles for 6 months after SOT [ 86 ]. The CMV-specific tetramers did not play a significant role in predicting CMV replication after SOT, because of small number of CMV viremia or disease [ 86 ].…”
Section: Cmv-cmimentioning
confidence: 99%
See 1 more Smart Citation
“…The commercially developed iTAg TM [Ni 2+ -nitrilotriacetic acid (NTA)–His-tag Chelate complexes] class I MHC Tetramers (Beckman Coulter, Krefeld, Germany) allow the staining of epitope-specific CD8 + T lymphocytes [ 85 ]. Mees et al evaluated the CMV-specific CD8 + T lymphocytes in 23 kidney transplant recipients using the CMV-specific iTAg TM class I pMHC Tetramers (Beckman Coulter, Germany) with the CMV-Ag specific pMHC-tetramers restricted by five different HLA-A and HLA-B alleles for 6 months after SOT [ 86 ]. The CMV-specific tetramers did not play a significant role in predicting CMV replication after SOT, because of small number of CMV viremia or disease [ 86 ].…”
Section: Cmv-cmimentioning
confidence: 99%
“…Mees et al evaluated the CMV-specific CD8 + T lymphocytes in 23 kidney transplant recipients using the CMV-specific iTAg TM class I pMHC Tetramers (Beckman Coulter, Germany) with the CMV-Ag specific pMHC-tetramers restricted by five different HLA-A and HLA-B alleles for 6 months after SOT [ 86 ]. The CMV-specific tetramers did not play a significant role in predicting CMV replication after SOT, because of small number of CMV viremia or disease [ 86 ]. A study by Brooimans et al suggested that the standardized single-platform iTAg TM class I CMV-specific pMHC Tetramer assays against the TCRs specific for the three different MHC class I CMV peptides were reproducible and useful for enumerating the CMV-specific T lymphocytes [ 87 ].…”
Section: Cmv-cmimentioning
confidence: 99%
“…Its combination with EBV-specific T-cell responses could allow a more precise assessment of patients at risk as well as of treatment efficacy. EBVspecific T-cell responses can be quantified by ELISPOT [101][102][103][104], ICS [105,106] and pMHC multimer staining [101,107] or by combining pMHC multimer staining and ICS techniques [106] in SOT recipients. A recent study compared five immunoassays [the functional EBV-specific IFN-␥ ELISPOT, ICS, ELISA and cytokine secretion assays (CSA) and the detection of EBV-specific T cells by pMHC multimer staining] in healthy subjects and identified the peptidebased IFN-␥ ELISPOT as the most accurate technique for immune monitoring and CSA for a more detailed phenotypic and functional analysis of T cells [74].…”
Section: Ebvmentioning
confidence: 99%